If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + -2(g + 4) = 8(g + -1) Reorder the terms: 3g + -2(4 + g) = 8(g + -1) 3g + (4 * -2 + g * -2) = 8(g + -1) 3g + (-8 + -2g) = 8(g + -1) Reorder the terms: -8 + 3g + -2g = 8(g + -1) Combine like terms: 3g + -2g = 1g -8 + 1g = 8(g + -1) Reorder the terms: -8 + 1g = 8(-1 + g) -8 + 1g = (-1 * 8 + g * 8) -8 + 1g = (-8 + 8g) Add '8' to each side of the equation. -8 + 8 + 1g = -8 + 8 + 8g Combine like terms: -8 + 8 = 0 0 + 1g = -8 + 8 + 8g 1g = -8 + 8 + 8g Combine like terms: -8 + 8 = 0 1g = 0 + 8g 1g = 8g Solving 1g = 8g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-8g' to each side of the equation. 1g + -8g = 8g + -8g Combine like terms: 1g + -8g = -7g -7g = 8g + -8g Combine like terms: 8g + -8g = 0 -7g = 0 Divide each side by '-7'. g = 0 Simplifying g = 0
| 7m=-35 | | 4(1+-3.5y)+2y=-2 | | -2f+6=10 | | 4e=32 | | 3x+5=69-5x | | 10n-8= | | 3m-6=5m+8 | | 16p=240 | | 3+7x=45+x | | 480=(7-1)c | | 2x-5=12x-95 | | 2x+7y=2 | | 3y^2+20y+73=0 | | 10x+41=1 | | -2x^2+6x=-40 | | 10n+6.2= | | 4(2.5+y)-4y=9 | | 2(11x+2y-2)+7x+4=180 | | X^2+5x+6-10x=0 | | m+3=-m-1 | | x*3= | | 5x+66=10x+11 | | 2(11x+2y+2)+7x+4=180 | | 14b=16b+72 | | X^2+5x+6=10x | | 12x+6=6x+24 | | 44.7-10n= | | -3x-4=11 | | 12x+-19=3x+8 | | 2x-2y=5 | | 1.10=(17+5)c | | 44.7-12n= |